Mobile Web-based Rural Information System for Tropical Fruits Diseases - Husain, Khaled Waled (2009)
The agricultural sector is an essential resource and important to any country,particularly, when it is the main source of income. Modern methods, treatments, the application of modern technology in agriculture and other information on how to care for and protect tropical fruits from diseases are useful to develop and generate wealth of rural areas, where most of the population works in agriculture. Majority of the population of countries are in the rural, and these people often do not have access and connectivity to computers and the Internet. However, more than 80% of the people in Malaysia have handphones. Thus this study will focus on the development of mobile web-based rural information system to help the farmers identify and seek solution to the problems like diseases faced in their agriculture produce.